Transhumanism and Society The Social Debate over Human Enhancement - Lilley, Stephen. (SpringerBriefs in Philosophy, 2013)
This book provides an introductory overview to the social debate over enhancement technologies with an overview of the transhumanists' call to bypass human nature and conservationists' argument in defense of it. The author present this controversy as it unfolds in the contest between transhumanists proponents and conservationists, who push back with an argument to conserve human nature and to ban enhancement technologies. This book provides an overview of the key contested points and present the debate in an orderly, constructive fashion. Readers are informed about the discussion over humanism, the tension between science and religion, and the interpretation of socio-technological revolutions; and are invited to make up their own mind about one of the most challenging topics concerning the social and ethical implications of technological advancements.